Prefeitura municipal de Santa Rosa/RS: patrimônio e paisagem - Haab, Vitor Matheus (2024)
This dissertation focuses on the analysis of Cultural Heritage, particularly the Municipal City Hall of Santa Rosa, located in the city of Santa Rosa, Rio Grande do Sul. Inaugurated in 1946 as the seat of government for many years, the building has become a notable symbol, standing out for its grandeur and architectural influences. This study, carried out within the Postgraduate Program in Cultural Heritage, in the thematic area of Architecture and Material Heritage, and the research line of Material Heritage Preservation, aimed at the general analysis of the building within its historical and cultural context, from its installation onwards, as well as the transformations and modifications over the years to the present, aiming to contribute to the promotion and valorization of Cultural Heritage through the development of a photographic and documentary exhibition on the identified historical aspects. Specifically, the study aimed to: discuss concepts related to Material Cultural Heritage; present a historical synthesis of the development of the city of Santa Rosa/RS; analyze the original architectural characteristics employed; simultaneously analyze, while problematizing, the process of its physical and social meaning transformations. Based on a qualitative approach using an exploratory-descriptive methodology, the study was divided into three stages: bibliographic and documentary research; compilation and organization of the proposed material; proposition of the development of the final product, photographic and documentary exhibition - Municipal City Hall of Santa Rosa/RS: Heritage and Landscape. The analysis of the building reveals its influence on urban development, especially in the "Cidade Alta," playing a crucial role in the cohesion and cultural identity of the area. Persistent structural issues are discussed, emphasizing the importance of community involvement in preservation against real estate pressures. Retrofitting is addressed as a conscious strategy to ensure continued relevance. Therefore, the proposition of the exhibition not only informs the analyzed information but also raises awareness and preserves Cultural Heritage, becoming a link between generations.